If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6z=4(1/2z-8
We move all terms to the left:
6z-(4(1/2z-8)=0
Domain of the equation: 2z-8)!=0We multiply all the terms by the denominator
z∈R
6z*2z-8)-(4(1=0
We add all the numbers together, and all the variables
6z*2z=0
Wy multiply elements
12z^2=0
a = 12; b = 0; c = 0;
Δ = b2-4ac
Δ = 02-4·12·0
Δ = 0
Delta is equal to zero, so there is only one solution to the equation
Stosujemy wzór:$z=\frac{-b}{2a}=\frac{0}{24}=0$
| q+239=-5q-7 | | 9c-4c=4 | | 75=x/36 | | -20y/20=-20 | | 7x+9-6x=12 | | Y=10x+23/11 | | 6s+11s=4 | | -2y+5=(3y-3) | | 2/15=3/2(4/9x+3) | | 2n+7=7n-3 | | -10g=9–7g | | 2/3x+14=1/3x+12 | | 5x-3(4-2x)+6=0 | | 0.8aa=7.5 | | 2/3x+1/11=-1/3x-1/3 | | k−8=11.8 | | 2c-8=c+14 | | 0.2x+3=0.27x+2.7 | | 8(3x+4)-5(6x)=20 | | -8+3r=3r-7 | | 9(c-8)+5=-67 | | −4.3g=25.8 | | −7.5(x−3)=3.75 | | 2/3=6/v | | x;3x-5=1/2x+2x= | | -9a+4=a+204 | | 5x/3x+5=2 | | -5a-8a=0 | | 8p-5=5p+7 | | 4(x-2)=(x+2) | | 9x+75=10x-20 | | 2(4x-4)+4x+5=-111 |